Geographical distribution of intestinal schistosomiasis and soil-transmitted helminthiasis and preventive chemotherapy strategies in Sierra Leone. - Joseph B Koroma; Jen Peterson; Aiah A Gbakima; Francis E Nylander; Foday Sahr; Ricardo J Soares Magalhães; Yaobi Zhang; Mary H Hodges (Public Library of Science (PLoS), 2010)
BACKGROUND: A national baseline mapping of schistosomiasis and soil-transmitted helminthiasis (STH) was performed in Sierra Leone. The aim was to provide necessary tools for the Ministry of Health and Sanitation to plan the intervention strategies in the national integrated control program on neglected tropical diseases according to the World Health Organization (WHO) guidelines for preventative chemotherapy (PCT) and for future monitoring and evaluation. METHODOLOGY/PRINCIPAL FINDINGS: 53 primary schools were randomly selected through a two-staged random sampling throughout the country. Approximately one hundred children aged 5-16 years of age were systematically selected from each school and their stool samples examined in a field laboratory. A total of 5,651 samples were examined. Data were analyzed with multivariable logistic regression models using model-based geostatistics. Spatial analysis predicted that S. mansoni infection was positively associated with population density and elevation and that there was a large cluster of high risk of S. mansoni infection (prevalence >70%) in the north and most of the eastern areas of the country, in line with the observed prevalence in Kono (63.8-78.3%), Koinadugu (21.6-82.1%), Kailahun (43.5-52.6%), Kenema (6.1-68.9%) and Tonkolili (0-57.3%). Hookworm infection was negatively associated with population density and land surface temperature, and was high across Sierra Leone with a large cluster of high infection risk (prevalence >70%) in the north-eastern part of the country. Remarkably low prevalence of Ascaris lumbricoides (7.2%) and Trichuris trichiura (3.3%) was recorded when compared with results published in the 1990s. CONCLUSIONS/SIGNIFICANCE: Results justify PCT for schistosomiasis for school age children and at-risk adults every year in high-risk communities in five districts and every two years in moderate-risk communities in one more district. The high prevalence of STH, particularly hookworm, coupled with widespread anemia according to a national report in Sierra Leone, suggests all but one district justifying biannual PCT for STH for pre-school children, school age children, and at-risk adults. PCT for STH in the remaining district, Kono is justified annually.